Grammatical Cohesion in Digital Fiction: A Study of Darkest Fears on Wattpad - Luh Putu Eka Elia Utari; Dewa Ayu Kadek Claria; I Nyoman Muliana (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2026)
This research investigates the types and functions of grammatical cohesion found in the story Darkest Fears on Wattpad. In this study, the theory proposed by Halliday and Hasan (1976) in their book Cohesion in English was applied as the analytical framework. The data source of this research is the Darkest Fears story on Wattpad, which consists of 29 chapters. A descriptive qualitative method was employed to address the research problem. The results show that all types of grammatical cohesion are present in the story, namely reference, substitution, ellipsis, and conjunction. Furthermore, each type performs different functions within the text. Reference functions as a directional device that helps readers understand the context being referred to. Substitution replaces elements in the text with alternative forms, while ellipsis omits elements by leaving them implicit or zero. Finally, conjunction functions to relate and connect elements within the text.